Genetic diversity of upland rice revealed by quantitative traits and microsatellite polymorphisms - Sohrabi, Mehdi (2012)
In Malaysia, upland rice is cultivated mainly in Sabah and Sarawak, and a small area in Peninsular Malaysia. In this study, the genetic diversity was evaluated among fifty Malaysian upland rice accessions. The objectives of this research were (i) to study the genetic diversity of the upland rice population revealed by quantitative traits and microsatellite polymorphism, (ii) to determine genetic control and heritability of quantitative traits, and (iii) to identify several potential upland rice accessions for further breeding program. In the first experiment the genetic diversity was evaluated based on 12 quantitative traits. All traits were significant or highly significant among all accessions. Four traits indicated both high level of broad sense heritability and genetic advance, namely flag leaf length to width ratio, spikelet fertility, grain yield, and days to flowering. All accessions were divided into six groups by morphological clustering and accessions 6040, 6041, 6048, 6068, 6070, and 6067 indicated higher average values for most of traits. This clustering was related to geographical divergence between Sabah state and Peninsular Malaysia. The twelve morphological traits provided around 77% variation among accessions. Twenty three SSR markers were used for estimation of genetic relationships, which finally helped in characterization of the upland rice germplasm.Ten primers indicated polymorphism among 50 accessions of upland rice. The Jaccard similarity coefficient between accessions was clustered in 7 groups which correlated to regional diversity. Shannon’s information index ranged from 0.5269 to 2.0050. Gene diversity (h) ranged from 0.3432 to 0.8273. Overall gene flow was 0.0011. Some accessions suggested for further breeding program according to their Jaccardʼs similarity. They are including accessions 07537, 07538, 03826, 07574, 07588, 07585, 07540, 07575, 07541, 07543, 07544, 07576, 07571, 07539, 03825, and 03830 from group six and also accessions 07531, 07534, and 07535 from group five.